Chaotic recurrence of the fixed assets-infrastructure influence on financial health of the hospitality industry in emerging markets (2014)
The influence of fixed assets (property, plant and equipment) and the quality of infrastructure in financial health was analyzed in the hospitality industry in emerging markets. Colombia was chosen as representative unit of CIVETS emerging market group. Financial health was determined by ratios of fixed assets net worth, fixed assets turnover and return on fixed assets. A recurrence analysis was applied, and recurrence plot, phase space and recurrence quantification analysis were all applied; first, to determine the influence of fixed assets on the financial health and second to determine the combined influence of infrastructures and fixed assets. Results showed that a non-linear and non-monotonic relationship exists between infrastructure and fixed assets with financial health. Investment in fixed assets and infrastructure leads to chaotic results making it difficult to make investment decisions in emerging markets.